2023
DOI: 10.52589/ajafr-f1wxfxu3
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Tax and Financial Performance: Evidence from Listed Consumer Goods Firms in Nigeria

Abstract: The study examined the effect of corporate tax on the financial performance of Nigerian listed consumer goods companies from 2011 to 2021. A sample of sixteen (16) consumer goods firms was used for the study. Secondary data source was generated from the annual reports of the selected firms. The random effect panel regression results revealed that company income tax negatively affects financial performance. The study also revealed that education tax has a significant positive effect on financial performance. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Study on company income tax in relation to financial performance in various sectors of the economy both in advanced and developing countries is inconclusive as many revealed positive and significant relationship while others revealed negative relationship. Study conducted by Williams, Onmonya, and Ebire (2023) on Nigeria listed consumer goods companies from 2011 to 2021 revealed that company income tax has negative effect on financial performance while education tax has a significant positive effect on financial performance. The study however, concluded that corporate tax has a statistically significant effect on the financial performance of consumer goods firms in Nigeria.…”
Section: Company Income Taxmentioning
confidence: 99%
See 1 more Smart Citation
“…Study on company income tax in relation to financial performance in various sectors of the economy both in advanced and developing countries is inconclusive as many revealed positive and significant relationship while others revealed negative relationship. Study conducted by Williams, Onmonya, and Ebire (2023) on Nigeria listed consumer goods companies from 2011 to 2021 revealed that company income tax has negative effect on financial performance while education tax has a significant positive effect on financial performance. The study however, concluded that corporate tax has a statistically significant effect on the financial performance of consumer goods firms in Nigeria.…”
Section: Company Income Taxmentioning
confidence: 99%
“…A lot have been written on taxation and performance of companies in Nigeria, with special reference to manufacturing industries, Oil and gas, banking and other financial institution (Taiwo & Oyedokun (2022) ' Lormbagah, Abiahu, & Ibiam (2021); Williams, Onmonya and Ebire, (2023)), yet very little research work focused on listed Information and Communications Technology (ICT) companies in the Nigeria. Reason adduced to this might be because of newness of this sector in Nigeria compared to other sectors of Nigeria's economy.…”
Section: Introductionmentioning
confidence: 99%